Measuring the satisfaction level of the postgraduate students on the scientific research process in Tishreen University (A field study of the postgraduate students in the Department of Sociology) - Mohammad, Osama (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aimed at identifying the reality of scientific research in Tishreen University from the perspective of postgraduate students in the Department of sociology, the study is divided into five key areas related to the process of scientific research which are: services and facilities, scientific staff, financing of scientific research, scientific research and community development, and the quality of scientific research. The researcher used the descriptive analytical method, comprehensive inventory method for all postgraduate students. A questionnaire was designed and distributed to the members of the universe. Data had been analyzed with the help of SPSS programme, Likert quintuple scale was also used to answer the questionnaire, in addition the test of averages and factor analysis was applied. The result of data analysis showed that the dissatisfaction of postgraduate students in the Department of Sociology on the reality of scientific research in University, and that the services and facilities and financing of scientific research are the most important factors from the perspective of postgraduate students in the Department of Sociology.